COVID-19 data representation in business databases. Issue 4 (2nd October 2022) - Vaaler, Alyson; Reiter, Lauren
Abstract: The presence of COVID-19 data in business databases is reflected by some providers making changes in how they collect, organize, share, and maintain data. These changes have implications for those who rely on business information for their decision-making or research. In this study, the authors sought to provide an overarching summary of ways business data providers are presenting COVID-19 data. Findings include the features used in business databases to address the impact of COVID-19 and considerations for librarians who work with business data.